2023
DOI: 10.1002/ueg2.12463
|View full text |Cite
|
Sign up to set email alerts
|

miR‐10b‐5p rescues leaky gut linked with gastrointestinal dysmotility and diabetes

Hannah Zogg,
Rajan Singh,
Se Eun Ha
et al.

Abstract: Background/AimDiabetes has substantive co‐occurrence with disorders of gut‐brain interactions (DGBIs). The pathophysiological and molecular mechanisms linking diabetes and DGBIs are unclear. MicroRNAs (miRNAs) are key regulators of diabetes and gut dysmotility. We investigated whether impaired gut barrier function is regulated by a key miRNA, miR‐10b‐5p, linking diabetes and gut dysmotility.MethodsWe created a new mouse line using the Mb3Cas12a/Mb3Cpf1 endonuclease to delete mir‐10b globally. Loss of function … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…Our results indicate that the long-term treatment of HFHSD-induced diabetic mice subcutaneously injected with miR-10a/b mimics can effectively rescue both diabetes and GI dysmotility without indication for increased risk of cancer development and inflammation induction. These efficacy and safety data are consistent with our previous studies [16,17] that highlighted the pivotal role of miR-10a/b-5p in regulating glucose homeostasis and GI motility as well as the promising efficacy of miR-10a/b mimics in reversing diabetes and GI dysmotility without induction of cancer.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Our results indicate that the long-term treatment of HFHSD-induced diabetic mice subcutaneously injected with miR-10a/b mimics can effectively rescue both diabetes and GI dysmotility without indication for increased risk of cancer development and inflammation induction. These efficacy and safety data are consistent with our previous studies [16,17] that highlighted the pivotal role of miR-10a/b-5p in regulating glucose homeostasis and GI motility as well as the promising efficacy of miR-10a/b mimics in reversing diabetes and GI dysmotility without induction of cancer.…”
Section: Discussionsupporting
confidence: 91%
“…We further found that loss of miR-10b-5p in KIT + β cells and ICC in Kit-mir-10b KO mice led to diabetes and GI dysmotility, revealing a novel miR-10b-KLF11-KIT pathway that regulates glucose homeostasis and GI motility [16]. In addition, we found that miR-10a-5p mimic and miR-10b-5p mimic (miR-10a/b mimics) intervention effectively reversed these pathological phenotypes in the multiple models of diabetic mice by restoration of β cells and ICC, highlighting the potential utilization of miR-10a/b mimics in therapeutic applications [16,17].…”
Section: Introductionmentioning
confidence: 79%
See 2 more Smart Citations
“…CCND2 [1083], VCAM1 [761], PDGFB (platelet derived growth factor subunit B) [1059], PTCH1 [1098], FOXQ1 [1044], IGF2BP1 [1162], ACTC1 [1192], DAPK1 [947], hsa-mir-2110 [1676], hsa-mir-10b-5p [1677], TCF3 [1678], NR1I2 [1679] and TRIM28 [1680] have been shown to be associated with inflammation. Studies have shown that CCND2 [1495], VCAM1 [1462], PTPRD (protein tyrosine phosphatase receptor type D) [1496], PRKCB (protein kinase C beta) [1476], IGF2BP1 [1545], hsa-mir-200a-3p [1681] and hsa-mir-10b-5p [1682] are an important biomarkers of diabetes mellitus. VCAM1 [110], PDGFB (platelet derived growth factor subunit B) [121], IGF2BP1 [162], DAPK1 [183] and hsa-mir-17-5p [1683] are a potential markers for the detection and prognosis of endometriosis.…”
Section: Discussionmentioning
confidence: 99%